Study of the water quality of basin Santa river - Romero Baylón, Alfonso (2010)
In the present paper called “Study of the quality of the water of the basin from the Santa river”, has been studied the polluted effect of the mining passive from Ticapampa that constituted a polimetalic tailing from flotation of sulfide minerals of copper, lead and zinc which has been located in the medium basin of the Santa river, that has been impacted from a negative way since 1900 for mining works of Collaracra, el Triunfo and La Florida; In 1908, by the performance of the Concentrate Plant and the smelting from the Mining Company “THE ANGLO FRENCH TICAPAMPA SILVER MINING CO”, and in 1967, for the mining works from the exploitation of silver, lead and zinc and the performance from the Concentrate Plant in charge of Mining Company Alianza S.A., National Enterprise; as a consequence of the development of mining works and activities of benefiting, there are environment passive, such as: four polimetalic tailing ponds and filtrations of water of the tailing, whose drainages pour directly to the body of water, main receptor of the basin of the Santa River, whose quality of waters has became in a place without aquatic life, that don’t lead the consumption of this water for has been very nocive for the living organism.